Establishment of rapd analysis protocol for Elephantopus scaber L. - Jaya Mania Rao, A/L Ramadoo @ Devudu. (Universiti Malaysia Sarawak (UNIMAS), 2006)
IElephul1topltS sc:uher L. is a pantropical weed, which is originally from America and can be !found locally through out Sarawak. The objective of this project is to establish a Random IAmplified Polymorphi ' DNA (RAPD) protocol for E.scclber. In this study. SDS and ('lAB genomic DNA extraction methods were used to extract DNA. Among the two extraction melhods SDS extraction method produced better quality and sufficient amount of DNA compared to CTAB method. Go d quality of bands of DNA recovery was observed on 1% agarose gel. Sets of primers OPA. OPB. and ope were used in the RAPD analysis and only OPAOS produced satisfactory result. Optimization was done on the concentration of magnesium chloride and annealing temperature of primers. The optimal annealing temperature and magnesium chloride concentration for OPAOS were 330e and 3mM respectively. This condition produced good and consistent RAPD pro files. NTSYSpc version 2.0 software (Rohlf, 1998) was used to analyze the protile in order to construct dendogram. Similarity matrix was generated based on Jaccard coefficient (Godwin el ul., 2001). This analysis revealed that the 10 individuals of E.scaher \"<cre clearly divided into clusters and there were genetic variations within these 10 individuals.